Accommodating visual art in a high-stakes public examination. Issue 1 (1st March 2015) - Stapleton, Hazel
This article discusses issues relating to the assessment of visual art in the Irish Leaving Certificate Examination, which is a high-stakes terminal examination for school leavers taken at the end of their secondary education. There is an expectation from stakeholders, which includes the students themselves, their parents and the users of the results that in a state-run examination every subject examined, be it mathematics or visual art, will conform to the basic principles of validity, reliability and freedom from bias. In order to achieve these aims for visual art as a subject, two conditions must be ensured: first, the assessment technique used must be a valid and reliable reporting mechanism for student achievement; and second the assessment of learning in art must be capable of standing up to equal rigour of inspection in its processes and techniques as do other subjects. The challenges of finding a model that is both 'art fair' and 'assessment fair' are identified along with some insightful research findings.